Dissemination of methodical experience in club activities by teacher of information technologies in Siauliai region - Kaklauskas, Liudvikas; Narkienė, Vilma (Lietuvos matematikos rinkinys, 2000)
The club was founded in October 1999. Its purpose is to help teachers of Information Technologies using new information technologies at school as well as spreading of teachers advanced experience, presenting innovations in informational technologies, creating possibilities to use specialised materials.